Effect of Nickel Addition and Porosity on Fracture Behaviour of Molybdenum Alloyed Powder Metallurgical Steel - (:unkn) unknown (CARL HANSER VERLAG, 2010)
In the study for this contribution, good mechanical properties have been obtained from Mo (and Cu) alloyed PM-steels after suitable heat treatment. The influence of two to four weight percent nickel additions in these Mo (and Cu) alloyed PM-steels on the mechanical properties have been studied. The influence of such an alloying modification on the defect characteristics has also been investigated. The heat treatment of the steel material has been realized via a novel way, i. e. with the sinter-hardening method. The mechanical properties like tensile strength, matrix microhardness, and toughness have been measured. Transverse rupture tests have been implemented for toughness measurement while the transverse rupture strength data has been obtained by using the Weibull statistics. Microstructural studies have been performed with various microscopy techniques, where the general steel matrix was observed to exist of tempered martensite, bainite, residual austenite, and micropores. The amount of pores was measured with image analysis technique, while the amount of retained austenite was measured with the magnetic saturation method. The results show that the values of the transverse rupture test are determined primarily by pores/pore agglomerates that fit big size defect criteria. On the other hand, a positive effect of increasing Nickel content has been observed on the resistance against fracture.